2019
DOI: 10.1177/2058738419828891
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress combined with lipopolysaccharide alter the activity and superficial molecules of peripheral monocytes

Abstract: The purpose of this study was to focus on the underlying relationship between the hyperactivity for the peripheral monocytes and heat stroke by investigating the inflammatory oxidative activity of and the expression of superficial molecules. Peripheral blood samples were collected from 10 healthy adult volunteers. Human blood monocytes were isolated by density gradient centrifugation and sequent adherent culture. The objectives were divided into four groups: 43°C heat stress combined with lipopolysaccharide (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In vitro studies have also demonstrated that heat stress decreases the phagocytic activities of immune cells. Under heat stress, the phagocytic activity of peripheral monocytes from humans is reduced after LPS stimulation [ 45 ]. In addition, decreased phagocytosis in bovine immune cells under hot conditions was demonstrated by using the opsonization of fluorescein-labeled Escherichia coli [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have also demonstrated that heat stress decreases the phagocytic activities of immune cells. Under heat stress, the phagocytic activity of peripheral monocytes from humans is reduced after LPS stimulation [ 45 ]. In addition, decreased phagocytosis in bovine immune cells under hot conditions was demonstrated by using the opsonization of fluorescein-labeled Escherichia coli [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress and lipopolysaccharide (HS + LPS) were employed to construct the in vitro models of heat stroke in our previous study. 16 All the HPMEC were categorized into four groups with eight wells in each group: control group (CON group), heat stroke group (HS group), heparanase group (HPSE group), and unfractionated heparin group (UFH group). After conventional culture for 72 h, the cell in the CON group was cultured in normal conditions, without receiving heat stress or LPS (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate HPMEC apoptosis and heparansulfate proteoglycan (HSPG) concentration, flow cytometry was performed in each group according to our previous methods. 16 Cells in each group were washed with phosphate‐buffered saline (PBS) for 15 min, centrifuged, and resuspended with 500 μL AnnexinV‐fluorescein isothiocyanate (FITC) (UElandy) binding buffer per tube. The cells were further stained with 5 μL AnnexinV‐FITC, then mixed and incubated in the dark at 4°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Pretreatment before molding Heat stress and lipopolysaccharide (HS+LPS) were employed to construct the in vitro models of heat stroke in our previous study. 15 . All the HPMEC were categorized into 4 groups with 8 wells in each group: control group (CON group), heat stroke group (HS group), heparanase group (HPSE group), and unfractionated heparin group (UFH group).…”
Section: Induction Of the Hpmec Under Heat Stress Combined With Lps I...mentioning
confidence: 99%